2003
DOI: 10.1074/jbc.m305232200
|View full text |Cite
|
Sign up to set email alerts
|

Janus Kinase 2 and Calcium Are Required for Angiotensin II-dependent Activation of Steroidogenic Acute Regulatory Protein Transcription in H295R Human Adrenocortical Cells

Abstract: Angiotensin II-and K ؉ -stimulated aldosterone production in the adrenocortical glomerulosa cells requires induction of the steroidogenic acute regulatory protein (StAR). While both agents activate Ca 2؉ signaling, the mechanisms leading to aldosterone synthesis are distinct, and the angiotensin II response cannot be mimicked by K ؉ . We previously reported that StAR mRNA levels and promoter-reporter gene activity in transiently transfected H295R human adrenocortical cells were stimulated by angiotensin II but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 58 publications
3
20
0
Order By: Relevance
“…Surprisingly, analysis of corticosterone production by isolated adrenal cells provided clear evidence that unlike PRL, JAK2 was involved in basal and ACTH-induced steroidogenesis. Previous data have already reported an early role of JAK2 in the mediation of hormone effects through action on G proteincoupled receptors including angiotensin receptor AGTR 1a in adrenocortical cells (19) or LH receptor LHCGR in ovarian cells (30). In follicular cells, JAK2 tyrosine phosphorylation was increased in response to LH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, analysis of corticosterone production by isolated adrenal cells provided clear evidence that unlike PRL, JAK2 was involved in basal and ACTH-induced steroidogenesis. Previous data have already reported an early role of JAK2 in the mediation of hormone effects through action on G proteincoupled receptors including angiotensin receptor AGTR 1a in adrenocortical cells (19) or LH receptor LHCGR in ovarian cells (30). In follicular cells, JAK2 tyrosine phosphorylation was increased in response to LH.…”
Section: Discussionmentioning
confidence: 99%
“…This effect of JAK2 is in part mediated through the MAPK/ERK1/2 pathway (19,33) even though the molecular target of JAK2 was not clearly identified in adrenal cells. Our data rather support the finding that in adrenocortical cells, activated JAK2 levels are not sensitive to ACTH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, CTRP1 did not increase the transcription of CYP11B1, the enzyme responsible for glucocorticoid synthesis. Previous reports found that Ang II increased the transcription of CYP11B1 and STAR (Li et al 2003, Romero et al 2004, and AT 1 R blockade had no effect, suggesting that this aldosterone secretion induced by CTRP-1 is independent of Ang II-mediated regulation mechanism (Jeon et al 2008).…”
Section: Ctrp-1 Complement-c1qmentioning
confidence: 99%
“…ERK1/2 are phosphorylated and activated by MEK1/2 (for review see Spät & Hunyady 2004). In aldosterone producing cells, Ang II was reported to activate the ERK, JNK and p38 MAPK pathways (Watanabe et al 1996, McNeill et al 1998, Tian et al 1998, Natarajan et al 2002, Gu et al 2003, Li et al 2003. Also, Ang II activated p42 MAPK via protein kinase C in bovine adrenal glomerulosa cells (Tian et al 1998).…”
Section: Introductionmentioning
confidence: 99%